A framework for quantifying the multisectoral burden of animal disease to support decision making - Lysholm, Sara; Chaters, G.L.; Di Bari, C.; Hughes, E.C.; Huntington, B.; Rushton, J.; Thomas, Lian F. (Frontiers Media, 2025)
Animal diseases have wide-ranging impacts in multiple societal arenas, including agriculture, public health and the environment. These diseases cause significant economic losses for farmers, disrupt food security and present zoonotic risks to human populations. Additionally, they contribute to antimicrobial resistance and a range of environmental issues such as greenhouse gas emissions. The societal and ecological costs of livestock diseases are frequently underrepresented or unaddressed in policy decisions and resource allocations. Social cost–benefit analysis (SCBA) offers a comprehensive framework to evaluate the broad impacts of animal diseases across different sectors. This approach aligns with the One Health concept, which seeks to integrate and optimize the health of humans, animals and the environment. Traditional economic evaluations often focus narrowly on profit maximization within the livestock sector, neglecting wider externalities such as public health and environmental impacts. In contrast, SCBA takes a multi-sectoral whole-system view, considering multiple factors to guide public and private sector investments toward maximizing societal benefits. This paper discusses three separate sector specific (Animal health, Human health, Environmental health) methodologies for quantifying the burden of animal diseases. It then discusses how these estimates can be combined to generate multisectoral estimates of the impacts of animal diseases on human societies and the environment using monetary values. Finally this paper explores how this framework can support the evaluation of interventions from a One Health perspective though SCBA. This integrated assessment framework supports informed decision-making and resource allocation, ultimately contributing to improved public health outcomes, enhanced animal welfare, and greater environmental sustainability.